Dendritic cells that phagocytose apoptotic macrophages loaded with mycobacterial antigens activate CD8 T cells via cross-presentation. - Patricia Espinosa-Cueto; Alejandro Magallanes-Puebla; Carlos Castellanos; Raul Mancilla (PLoS ONE)
While homeostatic apoptosis is immunologically silent, macrophage apoptosis during Mycobacterium tuberculosis infection can potentially induce an immune response against the mycobacteria. To examine the role of dendritic cells in this response, macrophage apoptosis was induced by incubating the macrophage with cell wall extracts of mycobacteria expressing LpqH. The apoptogenic proteins of the cell wall extracts were engulfed by the macrophage and then were translocated from the cytosol to the nuclei of the dying cells. Dendritic cells that engulfed the apoptotic macrophages acquired an immunogenic phenotype that included upregulation of MHC-I, increased expression of the costimulatory molecules, CD40, CD80, and CD86, and increased production of IL-12, IL-10, TNF-α, and TGF-β. In addition, the dendritic cells triggered a proliferative response of CD8+ T cells with IFN-γ production via cross-presentation. Taken together, these findings support a model in which phagocytosis of whole apoptotic cells carrying mycobacterial antigens promotes a potentially protective immune response.